Early rehabilitation after mastectomy - postisometric relaxation - M. P. Vavilov; E. V. Kizhaev; M. N. Kusevich; A. V. Martynenko (ABV-press, 2014)
Given postmastectomy, all the muscles of chest w all and humeroscapular region have been tested for the first time ever . Mentioned muscles spasms predominate over weakness of shoulder girdle lower clamps and of antagonist muscles. Postisometric relaxation of spastic muscles as well as the goal-directed gymnastics for relaxed muscles gives good results in early rehabilitation after mastectomy.